ANALISIS PENGGUNAAN BAHASA GAUL TERHADAP BAHASA INDONESIA DI KALANGAN REMAJA - Ines Tasya Jadidah; Vanesha Putri Pramudita; Maryatul Kiftiah; Shinta Bela; Fitriah Isnaini (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
Language is a tool that humans use to communicate by conveying their thoughts and desires towards other people to the person they are talking to. In Indonesia, especially among teenagers, slang is very popular in their daily lives. This slang is a language that is only understood by those who use it, especially teenagers, because the most popular use of slang is in the hands of teenagers. This research use desciptive qualitative approach. The subjects in this research were teenagers at home and active students at the Raden Fatah State Islamic University in Palembang and we took several respondents to be interviewed. We used two methods or techniques for collecting data, namely by observation and interviews with several respondents. From the interviews that have been conducted, researchers can analyze that teenagers nowadays often use slang, they say that slang can make it easier for them to communicate with each other and make each other more familiar. The answers from several respondents we interviewed sometimes unconsciously used slang and Indonesian at the same time or mixed up the two, for example "You are really SKSD, aren't you?" From the results of the analysis explained in the discussion section, the researcher can draw the conclusion that the use of slang which is currently very varied has a great influence on the existence (existence) of Indonesian itself as the identity of the Indonesian state, because teenagers are more accustomed to using slang than Indonesian. itself because it could cause the Indonesian language to fade and not be sustainable.